2014
DOI: 10.18632/oncotarget.2659
|View full text |Cite
|
Sign up to set email alerts
|

DEPTOR has growth suppression activity against pancreatic cancer cells

Abstract: DEPTOR was reported as a naturally occurring inhibitor of mTORC1 and mTORC2. The role of DEPTOR in the growth and survival of pancreatic cancer cells has not previously been determined. Here we report that while DEPTOR shows a cytoplasmic expression in both normal pancreatic acinar and islet cells in a patchy manner, its expression is reduced in PanIN1 and PanIN2 and completely lost in 100 out of 101 pancreatic ductal adenocarcinoma (PDAC) tissues. Ectopic DEPTOR expression in two pancreatic cancer cell lines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 30 publications
(40 reference statements)
2
39
0
Order By: Relevance
“…The role of DEPTOR expression in the progression of human malignancies is still controversial; this may be because the regulation of DEPTOR is complicated in different individuals and tissues (28,31), as two opposite results were obtained in the same myeloma cells (31,58). In lung adenocarcinoma, there is still no direct evidence that DEPTOR regulates tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of DEPTOR expression in the progression of human malignancies is still controversial; this may be because the regulation of DEPTOR is complicated in different individuals and tissues (28,31), as two opposite results were obtained in the same myeloma cells (31,58). In lung adenocarcinoma, there is still no direct evidence that DEPTOR regulates tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Various mTOR inhibitors have been used in trials for cancer therapeutic (25,26). DEP domain-containing mTOR-interacting protein (DEPTOR), as a naturally occurring inhibitor of mTOR, usually acts as a tumor suppressor by blocking the activation of mTOR to inhibit cell proliferation, invasion, and survival effect of AKT (27,28). However, under certain circumstances, DEPTOR could act as an oncogene by relieving the feedback inhibition of mTOR, activation of mTOR enhances the downstream S6K expression, which could negatively regulate AKT via downregulating expression of IRS-1/2 (27,29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various functions of DEPTOR in cancer progression have been reported. Ectopic expression of the DEPTOR gene is known to reduce mTORC1 activity and cell growth in pancreatic cancer cells (Li et al, 2014). Here, we showed that knockdown of DEPTOR mRNA enhanced phosphorylation degree of S6K and protein level of cyclin D1 in prostate cancer LNCaP cells.…”
Section: Androgen Receptor Dependent Repression Of Deptor Mrna Expresmentioning
confidence: 71%
“…DEPTOR is suggested to be a tumor suppressor due to the inhibitory effect on mTORC1 and mTORC2 pathways. Recently, the post-translational regulation of DEPTOR was reported (Peterson et al, 2009;Li et al, 2014;Zhao et al, 2011;Gao et al, 2011). DEPTOR was phosphorylated by casein kinase 1 alpha, facilitating ubiquitylation by the F box protein SCF (βTrCP) (Duan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%